Caracterização sistemática do gênero Moenkhausia Eigenmann, 1903 (Characiformes, Characidae) - Raio, Cibele Bender [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The species currently allocated in Moenkhausia are not a monophyletic group. Current studies try to establish new relationships and adequation these species. However, identifications mistakes are usualy verified. What show wrong relationships. This study gathers the taxonomic knowledge of Moenkhausia, fixe, standardizes and complements species descriptions. Most species were grouped into groups, based on characters from the external morphology and phylogenetic knowledge available to the genre: Moenkhausia oligolepis – reticulate patters, presence of dark colored band on the caudal peduncle; M. lepidura – dark spot restricted to the upper lobe of the caudal fin; M. dichroura - spot in both lobes of caudal fin; M. doceana – one horizontally extended humeral spot or two humeral spot, spot presence in the caudal peduncle or in the middle rays of the caudal fin, six or more series of scales above lateral line; M. xinguensis - deep body at origin of dorsal fin, absent or inconspicuous humeral spot, five series of scales above lateral line; M. eigenmanni - concentration of chromatophores on the scales, especially in the middle part of the flanks, usually long body and characteristically convex pre-dorsal region; M. ceros - low concentration of chromatophores on the scales, small, dark or iridescent line from the middle region of the body to the caudal peduncle or middle rays of the caudal fin. These groupings are not natural and should not be taken as phylogenetic relationships. However, they are effective for species identification and development of future hypotheses of relationships in Moenkhausia

As espécies atualmente alocadas em Moenkhausia não formam um grupo monofilético. Estudos atuais buscam estabelecer novas relações e readequações destas espécies. No entanto, são verificados equívocos nas identificações que levam à relações não verdadeiras. O presente estudo reúne o conhecimento taxonômico sobre Moenkhausia, corrige, complementa e padroniza descrições das espécies. As espécies foram reunidas em grupos, com base em caracteres da morfologia externa e no conhecimento filogenético disponível para o gênero: Moenkhausia oligolepis - padrão de colorido reticulado e presença de banda escura no pedúnculo caudal; M. lepidura - mácula restrita ao lobo superior da nadadeira caudal; M. dichroura - mácula em ambos os lobos da nadadeira caudal; M. doceana - mácula umeral estendida horizontalmente ou duas máculas umerais, mácula no pedúnculo caudal ou nos raios medianos da nadadeira caudal; seis, ou mais, séries de escamas acima da linha lateral; M. xinguensis - maior altura do corpo na origem da nadadeira dorsal, mácula umeral ausente ou inconspícua e cinco series de escamas acima da linha lateral; M. eigenmanni - concentração de cromatóforos nas escamas, especialmente na região mediana dos flancos; corpo, geralmente, longo e caracteristicamente convexo na região pré-dorsal; M. ceros - baixa concentração de cromatóforos nas escamas, pequeno porte, faixa escura ou iridescente desde a região mediana do corpo ao pedúnculo caudal ou raios medianos da nadadeira caudal. Esses agrupamentos não são exclusivamente naturais e não devem ser tomados como relações filogenéticas. No entanto, são eficazes para a identificação das espécies e elaboração de futuras hipóteses de relações em Moenkhausia
Systematic characterization of the genus Moenkhausia Eigenmann, 1903 (Characiformes, Characidae)
Keywords: Taxonomia numerica; Characideo; Peixe - Classificação; Fishes - Classification